Community-based perceptions of emergency care in communities lacking formalised emergency medicine systems - Broccoli, Morgan Carol (Division of Emergency Medicine, 2015)
Kenya and Zambia face an increasing burden of emergent disease, with a high incidence of communicable diseases, increasing prevalence of non-communicable diseases and traumatic injuries. However, neither country has an integrated emergency care system that provides community access to high-quality emergency services. There has been recent interest in strengthening the emergency care systems in these countries, but before any interventions are implemented, an assessment of the current need for emergency care must be conducted, as the burden of acute disease and barriers to accessing emergency care in Zambia and Kenya remain largely undocumented. Aims and Objectives: The aim of this project was to ascertain community-based perceptions of the critical interventions necessary to improve access to emergency care in Zambia and Kenya, with the following objectives: 1. Determine the current pattern of out-of-hospital emergency care delivery at the community level. 2. Identify the communities’ experiences with emergency conditions and the barriers they face when trying to access care. 3. Discover community-generated solutions to the paucity of emergency care in urban and rural settings. Methods: Semi-structured focus groups were piloted in Zambia with 200 participants. Results were analysed with subsequent tool refinement for Kenya. Data were collected via focus groups with 600 urban and rural community members in cities and rural villages in the 8 Kenyan provinces. Thematic analysis of community member focus groups identified frequency of emergencies, perceptions of emergency care, perceived barriers to emergency care, and ideas for potential interventions. Results: Analysis of the focus group data identified several common themes. Community members in Zambia and Kenya experience a wide range of medical emergencies, and they rely on family members, neighbours, and Good Samaritans for assistance. These community members frequently provide assistance with transportation to medical facilities, and also attempt some basic first aid. These communities are already assisting one another during emergencies, and are willing to help in the future. Participants in this study also identified several barriers to emergency care : a lack of community education, absent or non-functional communication systems, insufficient transportation, no triage system, a lack of healthcare providers trained in emergency care, and inadequate equipment and supplies. Conclusions: Community members in Zambia and Kenya experience a wide range of medical emergencies. There is substantial reliance on family members and neighbours for assistance, commonly with transportation. Creating community education initiatives, identifying novel transportation solutions, implementing triage in healthcare facilities, and improving receiving facility care were community-identified solutions to barriers to emergency care.